Human induced vibrations in floors. Background documentation - M. Feldmann (2008)
This document provides background information to "Vibration Design ofFloors - Guideline". It presents alternative and more general ways for thedetermination of the floor response to dynamic human induced forces.The theoretical methods presented here and in the guideline document havebeen elaborated/investigated in the RFCS-Project "Vibration of Floors". Theguideline and background document are here disseminated under the grantof the Research fund for Coal and Steel within the project "HIVOSS".